Ultrastable Multiclock Frequency Injection and Dissemination in a Ring Fiber Network - Jialiang Wang; Wei Chen; Qin Liu; Nan Cheng; Zitong Feng; Fei Yang; Youzhen Gui; Haiwen Cai (IEEE Photonics Journal)
Owing to the characteristics of ultralow loss and antielectromagnetic interference, using optical fiber to deliver time and frequency signals has been a preferred choice for high-precision clock dissemination and comparison. As a brilliant idea, one has been able to reproduce ultrastable signals from one local station to multiple users. In this paper, we take a step further and propose a concept of multiclock (in different locations) dissemination for multiterminals. By injecting frequency signals into one stabilized ring-like fiber network, the relative stabilities of 3.4 × 10−14@1 s for a master clock dissemination and 5.1 × 10−14 @1 s for a slave clock dissemination have been achieved. The proposed scheme can greatly simplify the future “N” to “N” radio-frequency dissemination network, especially in the situation of multiclock comparison.